2017
DOI: 10.1099/jmm.0.000489
|View full text |Cite
|
Sign up to set email alerts
|

How do the epidemiology of paediatric methicillin-resistant Staphylococcus aureus and methicillin-susceptible Staphylococcus aureus bacteraemia differ?

Abstract: Our analysis indicates that S. aureus bacteraemia in <1-year-olds is primarily healthcare-associated, unlike MSSA bacteraemia in older age groups. Paediatric-specific interventions targeted at the healthcare setting, such as neonatal unit-specific care bundles and paediatric device-specific strategies, are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Hamdy et al also demonstrated that foci such as OM (31%), catheter-related infection (22%), SSTI (16%) and pneumonia (9%) are predominant 31 in a cohort of children with bacteremia caused by MRSA. Abernethy et al, in turn, reported that most bacteremia cases caused by MSSA originated from SSTI 33 ; this is similar to what has been reported in this study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Hamdy et al also demonstrated that foci such as OM (31%), catheter-related infection (22%), SSTI (16%) and pneumonia (9%) are predominant 31 in a cohort of children with bacteremia caused by MRSA. Abernethy et al, in turn, reported that most bacteremia cases caused by MSSA originated from SSTI 33 ; this is similar to what has been reported in this study.…”
Section: Discussionsupporting
confidence: 91%
“… 31 In children, community-based S. aureus bacteremia is more frequent and is associated with concomitant foci of infection 30 , 32 while healthcare-associated bacteremia is more commonly observed in neonates under the age of one and usually related to intravascular devices. 33 Significant risk factors were found based on the origin of secondary bacteremia; osteoarticular and pulmonary foci are at increased risk of secondary bacteremia due to MRSA. Hamdy et al also demonstrated that foci such as OM (31%), catheter-related infection (22%), SSTI (16%) and pneumonia (9%) are predominant 31 in a cohort of children with bacteremia caused by MRSA.…”
Section: Discussionmentioning
confidence: 99%